Optical thin film and preparation method thereof

By using blended polymer as the base film layer in the optical film and combining plasma treatment and sputtering coating technology, the problems of unsmoothing and insufficient bonding force of the film layer are solved, and an optical film with high mechanical strength, excellent optical performance and good thermal stability are achieved.

CN119530736APending Publication Date: 2025-02-28ZHEJIANG TAIYANG LITHIUM BATTERY MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411709861.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

In existing optical films, the interface between the film layers is not smooth or uneven, resulting in increased scattering and affecting transmission and reflection properties. The bonding force between the film and the base layer or different film layers is insufficient, which easily leads to peeling or cracks, affecting long-term stability.

Method used

The blend of polyimide, polycarbonate and polymethyl methacrylate is used as the base film layer, and a uniform film layer structure is formed by melt extrusion, and plasma treatment is performed to improve the adhesion of the plating layer. Then, high-quality SiO2 and TiO2 coatings are formed by two sputtering treatments to achieve excellent optical transmittance and anti-reflection properties.

Benefits of technology

It significantly improves the overall performance of the optical film, improves the mechanical strength, optical transparency and thermal stability of the film layer, enhances the film's oxidation resistance, moisture resistance and environmental adaptability, and ensures long-term stability and efficient optical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005155394590000151
    Figure BDA0005155394590000151
Patent Text Reader

Abstract

The invention relates to the technical field of optical thin films, and provides an optical thin film and a preparation method thereof.The preparation method comprises the steps that S100, polyimide, polycarbonate and polymethyl methacrylate are blended and then subjected to melt extrusion, and a base film layer is obtained; and S200, sequentially performing plasma treatment and sputtering treatment on the base film layer to obtain the optical thin film, wherein S200 comprises the following steps: S210, adopting oxygen as plasma gas, performing plasma treatment on the base film layer, and cooling to room temperature to obtain a first intermediate film layer; s220, carrying out first sputtering treatment on the first intermediate film layer by adopting a silicon dioxide target material in an argon atmosphere to obtain a second intermediate film layer; and S230, carrying out second sputtering treatment on the second intermediate film layer by adopting a titanium target material in a mixed gas atmosphere of argon and oxygen to obtain the optical thin film. According to the method, material blending, plasma treatment and sputtering treatment are adopted, and the overall performance of the optical thin film is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of optical films, and in particular to an optical film and a preparation method thereof. Background Art

[0002] Optical thin film refers to a thin film with specific optical functions that is deposited on the surface of a substrate by vacuum evaporation, sputtering, chemical vapor deposition (CVD), etc. Optical thin films are widely used in optical devices. When light passes through an optical thin film, due to the thickness, refractive index and wavelength of the thin film, the light wave will be reflected and transmitted at the interface of the film layer, thereby achieving the desired optical effect.

[0003] Optical films are usually composed of multiple thin layers, and the interface quality between each layer has an important influence on the final optical performance. However, in current optical films, the interface between the film layers is not smooth or uniform, which may increase scattering, thereby affecting the transmission and reflection properties of the film; the bonding strength between the film and the base layer or between different film layers is not enough, which is prone to peeling or cracking, affecting the long-term stability of the film. Therefore, it is urgent to provide an optical film with better bonding between the layers. Summary of the invention

[0004] The present invention aims to solve at least one of the above technical problems.

[0005] To this end, the first object of the present invention is to provide a method for preparing an optical film;

[0006] A second object of the present invention is to provide an optical film.

[0007] To achieve the first object of the present invention, the present invention provides a method for preparing an optical film, comprising:

[0008] S100, blending polyimide, polycarbonate, and polymethyl methacrylate and then melt-extrude the mixture to obtain a base film layer;

[0009] S200, sequentially performing plasma treatment and sputtering treatment on the base film layer to obtain an optical thin film;

[0010] Among them, S200 includes:

[0011] S210, using oxygen as plasma gas to perform plasma treatment on the base film layer, and then cooling to room temperature to obtain a first intermediate film layer;

[0012] S220, performing a first sputtering treatment on the first intermediate film layer in an argon atmosphere using a silicon dioxide target to obtain a second intermediate film layer;

[0013] S230, using a titanium target material to perform a second sputtering treatment on the second intermediate film layer in a mixed gas atmosphere of argon and oxygen to obtain an optical thin film.

[0014] Compared with the prior art, the technical effects achieved by adopting this technical solution are as follows: the present invention adopts material blending, plasma treatment and sputtering treatment to significantly improve the overall performance of the optical film. First, polyimide, polycarbonate and polymethyl methacrylate are blended. The blending of the three polymers combines their respective advantages to form a base film layer with high mechanical strength, good optical transparency and good thermal stability, which is suitable for multi-band optical applications. Melt extrusion can provide a uniform film structure for the optical film to avoid the degradation of optical performance caused by uneven mixing; plasma treatment can improve the adhesion of the base film layer to the sputtered coating and prevent the film layer from peeling off. Oxygen is used as the plasma gas to introduce oxygen groups to activate the surface of the base film layer, increase the surface free energy and improve the affinity; the sputtering area can deposit the film at a lower temperature to avoid thermal damage to the flexible substrate material. At the same time, the sputtered film layer can cover the irregular surface more evenly. , improving the optical properties of the film; the first sputtering treatment is the deposition of a silicon dioxide layer, which uses a silicon dioxide (SiO2) target material for sputtering deposition in an argon atmosphere, which can form a highly transparent, low-refractive index first coating, which can provide anti-reflection function for the optical film, reduce light loss, enhance the optical film's antioxidant and moisture resistance, and improve environmental adaptability; the second sputtering treatment is the deposition of a titanium dioxide layer, which uses a titanium target material for sputtering deposition in an argon and oxygen mixed gas to generate a high-refractive index titanium dioxide (TiO2) film layer, and the interference effect is achieved by alternating high-refractive index TiO2 layers with low-refractive index SiO2 layers, thereby improving multi-band optical performance; the base film layer of the optical film of the present invention optimizes the mechanical properties and optical properties through a melt blending method, and at the same time improves the coating adhesion through plasma treatment; two layers of sputtered coatings are formed through two sputtering treatments, giving the film excellent optical transmittance and anti-reflection properties.

[0015] In addition, the technical solution provided by the present invention may also have the following technical features:

[0016] In the above technical features, in S210, the gas flow rate of oxygen is 20sccm-50sccm; and / or the power of plasma treatment is 60W-100W; and / or the pressure of plasma treatment is 0.1Torr-0.5Torr; and / or the time of plasma treatment is 1min-3min.

[0017] Compared with the prior art, the technical effects achieved by adopting this technical solution are as follows: the oxygen flow rate determines the concentration of oxygen ions and free radicals in the plasma, thereby affecting the degree of chemical activation on the surface of the base film layer. The appropriate oxygen flow rate can balance the surface etching and activation effects, and avoid damage to the base film layer while forming oxygen groups; the power of plasma treatment is 60W-100W, which can ensure that the plasma can effectively excite oxygen molecules to produce active seeds and achieve efficient surface modification. It can also uniformly generate active groups and improve adhesion performance without damaging the mechanical properties of the base film layer; the pressure of plasma treatment is 0.1Torr-0.5Torr, which can balance the ion density and free radical concentration. degree and active ion energy to ensure sufficient surface modification depth, avoid damage to the base film surface due to excessive energy input, generate uniform plasma, ensure consistent surface modification of the entire base film layer, and improve the optical properties and uniformity of the overall film; the plasma treatment time is 1min-3min, and a large number of oxygen groups can be generated on the surface of the base film layer through plasma activation to form a uniform high-activity surface, ensuring that the subsequent sputtering layer forms a strong bond with the base film layer without having a significant negative impact on the mechanical properties of the base film layer; the surface after oxygen plasma treatment has better uniformity, the deposition rate of SiO2 and TiO2 layers is more stable during sputtering, and the film defects are reduced.

[0018] In any of the above technical features, in S220, the gas flow rate of argon gas is 20sccm-40sccm; and / or the power of the first sputtering process is 100W-300W; and / or the pressure of the first sputtering process is 2Torr-6Torr.

[0019] Compared with the prior art, the technical effects achieved by adopting this technical solution are as follows: the first sputtering treatment adopts SiO2 target material for sputtering treatment, and by optimizing key parameters such as argon gas flow rate, power and pressure, it can ensure that the film has a high-quality low-refractive index SiO2 layer, and improve the optical and mechanical properties of the film; the gas flow rate of argon gas is 20sccm-40sccm, which balances the sputtering rate and the film quality, can maintain a stable plasma, improve the sputtering efficiency, avoid excessive plasma scattering caused by excessive gas flow, thereby forming an uneven film layer, and ensure excellent optical properties and mechanical strength; the power of the first sputtering treatment is 100W-300W, which can generate a high-quality SiO2 film layer with a smooth and crack-free film surface and stable optical properties, which helps to prevent the problem of film granulation or base film damage caused by excessive power, and can meet the light transmittance and mechanical stability at the same time; the pressure of the first sputtering treatment is 2Torr-6Torr, the sputtering efficiency is improved, the uniform deposition of the film can be completed faster, and a dense SiO2 film layer can be formed with better wear resistance and corrosion resistance.

[0020] In any of the above technical features, in S230, the gas flow rate of argon is 20sccm-40sccm; and / or the gas flow rate of oxygen is 5sccm-15sccm; and / or the power of the second sputtering process is 100W-300W; and / or the pressure of the second sputtering process is 2Torr-6Torr.

[0021] Compared with the prior art, the technical effects achieved by adopting this technical solution are as follows: the gas flow rate of argon is 20sccm-40sccm, which can form a dense film structure while ensuring the sputtering rate, maintain the uniformity of plasma during the sputtering process, and ensure the uniform thickness and consistent optical properties of the film; the gas flow rate of oxygen is 5sccm-15sccm. Oxygen is a necessary component for the formation of TiO2 film. A reasonable oxygen concentration can obtain a uniform, highly transparent TiO2 film, improve the optical transmittance of the film, prevent excessive stress in the film, and avoid cracks or peeling; the power of the second sputtering treatment is 100W-300W, which can generate a smooth and uniform TiO2 film with a high refractive index and stable optical properties, avoiding excessive power causing film granulation or base film damage; the pressure of the second sputtering treatment is 2Torr-6Torr, which accelerates the deposition rate, forms a dense, smooth, high-refractive-index TiO2 film, and maintains a certain film uniformity.

[0022] In any of the above technical features, between S220 and S230, the following is also included:

[0023] S221, performing annealing treatment on the second intermediate film layer.

[0024] Compared with the prior art, the technical effects achieved by adopting this technical solution are as follows: adding annealing treatment between S220 and S230 and heat treating the second intermediate film layer can effectively improve the performance of the film layer. Annealing can make the film layer more stable and the interface with the base film layer or the subsequent film layer stronger. During the first sputtering process, the initial structure of the SiO2 film may have more pores or low density. Annealing can improve the density of the film layer by promoting the sintering of particles and crystal rearrangement, thereby enhancing its mechanical strength, wear resistance and corrosion resistance. Annealing treatment can also reduce the roughness of the film surface, making the surface smoother, which is conducive to the uniform deposition of the subsequent TiO2 film layer.

[0025] In any of the above technical features, the annealing treatment is carried out in an oxygen atmosphere; and / or the annealing treatment temperature is 300°C-500°C; and / or the annealing treatment time is 1h-3h.

[0026] Compared with the prior art, the technical effects achieved by adopting this technical solution are as follows: the oxygen atmosphere provides sufficient oxidation environment for the stoichiometric ratio of the film, the suboxide in the film is oxidized, ensuring the formation of high-purity SiO2, thereby improving the optical properties, and the pure oxide film layer is more stable, and has stronger anti-aging ability in high temperature, high humidity or chemical corrosion environment; the annealing temperature is 300℃-500℃, which can make it smoother and prevent the degradation of the film substrate caused by high temperature, while also enhancing the mechanical strength, wear resistance and high temperature resistance of the film, and improving the anti-reflection performance of the optical film; the annealing time is 1h-3h, which is sufficient to complete the oxidation densification of the surface layer of the film, promote the oxidation reaction and molecular rearrangement in the deep layer of the film, ensure the accuracy of the stoichiometric ratio, provide sufficient energy to release the internal stress of the film, and improve the crack resistance and mechanical stability of the film layer.

[0027] In any of the above technical features, in S200, after the sputtering treatment, the method further comprises: using a modified nano titanium dioxide solution for coating treatment; the preparation method of the modified nano titanium dioxide solution comprises:

[0028] S201, dissolving nano titanium dioxide in an ethanol aqueous solution, adjusting the pH, and performing a first stirring treatment to obtain a nano titanium dioxide solution;

[0029] S202, adding the hexadecyltrimethoxysilane solution dropwise to the nano-titanium dioxide solution, and performing centrifugal treatment and purification treatment in sequence to obtain a modified nano-titanium dioxide solution.

[0030] Compared with the prior art, the technical effect achieved by adopting this technical scheme is as follows: hexadecyltrimethoxysilane (HDTMS) is a surfactant, and its silane group reacts with the active hydroxyl group on the surface of nano-titanium dioxide to form a stable chemical bond. After modification, a hydrophobic organic molecular layer is formed on the surface of the nano-titanium dioxide particles, which improves its dispersibility and coating stability in the solution. The contact angle of the hydrophobic molecular layer surface is greater than 120°, which improves the anti-fouling performance of the titanium dioxide coating. The size of the modified nano-titanium dioxide particles is maintained in the range of 20-30nm, which is conducive to the formation of a uniform coating. The coating with modified nano-titanium dioxide solution not only significantly enhances the anti-fouling, UV protection and weather resistance of the optical film, but also further optimizes its optical properties and mechanical stability.

[0031] In any of the above technical features, the mass ratio of nano-titanium dioxide to ethanol aqueous solution is 1: (10-25); and / or the pH is adjusted to 4-5; and / or the rotation speed of the first stirring treatment is 450rpm-500rpm; and / or the time of the first stirring treatment is 4h-5h; and / or the concentration of hexadecyltrimethoxysilane solution is 15wt.%; and / or the purification treatment is repeated 2-3 times.

[0032] Compared with the prior art, the technical effects achieved by the technical solution are as follows: the mass ratio of nano-titanium dioxide to ethanol aqueous solution is 1: (10-25), which can effectively disperse nano-titanium dioxide; the surface of nano-titanium dioxide particles usually contains a large number of hydroxyl groups, and its surface activity is optimal under acidic conditions. Therefore, adjusting the pH to 4-5 is conducive to the hydrolysis and condensation reaction of hexadecyltrimethoxysilane, improving the modification efficiency, and providing a uniform particle base for the subsequent silane coupling agent reaction; the speed of the first stirring treatment is 450rpm-500rpm, which can be used in nano-titanium dioxide. During the dispersion of nano-titanium dioxide, appropriate shear force is provided to prevent particle agglomeration and ensure stirring uniformity; the first stirring treatment time is 4h-5h to ensure that the nano-titanium dioxide is evenly dispersed in the solution and avoid local agglomeration in a high-concentration system; the concentration of the hexadecyltrimethoxysilane solution is 15wt.%, which can not only provide sufficient silane coupling agent to participate in the reaction, but also avoid excessive reaction leading to secondary coverage of the particle surface; the purification treatment is repeated 2-3 times to effectively remove unreacted HDTMS and other impurities to ensure the purity of the modified layer.

[0033] In any of the above technical features, in S100, the mass ratio of polyimide, polycarbonate, and polymethyl methacrylate is (6-7):(2-3):1.

[0034] Compared with the prior art, the technical effect achieved by adopting this technical scheme is as follows: the mass ratio of polyimide, polycarbonate, and polymethyl methacrylate is (6-7): (2-3): 1, so that the heat resistance of the base film layer can reach 300°C, which is suitable for sputtering coating and subsequent heat treatment processes. The high proportion of polyimide provides sufficient rigidity, and the appropriate amount of polycarbonate and polymethyl methacrylate is added to improve flexibility. The base film layer exhibits good mechanical stability under bending and impact conditions; the addition of polycarbonate and polymethyl methacrylate ensures high light transmittance and meets the multi-band response requirements of optical films; the refractive index can be adjusted to 1.5-1.6 after the materials are mixed, which is suitable for the design requirements of multi-layer films.

[0035] To achieve the second objective of the present invention, the present invention further provides an optical film, which is prepared by the preparation method in any of the above technical solutions.

[0036] The optical film of the present invention includes the one obtained by the method for preparing the optical film in any technical solution of the present invention. The optical film of the present invention has all the beneficial effects of the method for preparing the optical film in any technical solution of the present invention, which will not be described in detail here.

[0037] After adopting the technical solution of the present invention, the following technical effects can be achieved:

[0038] 1. The base film layer of the optical film of the present invention optimizes the mechanical properties and optical properties by melt blending, and improves the coating adhesion by plasma treatment; two layers of sputtering coating are formed by two sputtering treatments, giving the film excellent optical transmittance and anti-reflection properties;

[0039] 2. Plasma treatment can improve the adhesion of the base film layer to the sputtered coating and prevent the film layer from peeling off. Using oxygen as the plasma gas can introduce oxygen groups to activate the surface of the base film layer, increase the surface free energy, and improve the affinity;

[0040] 3. The first sputtering treatment can form a first coating with high transparency and low refractive index, which can provide anti-reflection function for the optical film, reduce light loss, enhance the anti-oxidation and anti-humidity ability of the optical film, and improve environmental adaptability;

[0041] 4. The second sputtering process generates a high-refractive-index TiO2 film layer. By alternating high-refractive-index TiO2 layers with low-refractive-index SiO2 layers, interference effects are achieved to improve multi-band optical performance. DETAILED DESCRIPTION

[0042] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and understandable, the technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] In the related art, optical films are usually composed of multiple thin layers, and the interface quality between each layer has an important influence on the final optical performance. However, the current optical film has insufficient bonding strength with the base layer or different film layers, which is prone to peeling or cracking, affecting the long-term stability of the film; in view of this, the present invention provides an optical film and a preparation method thereof, which improves the adhesion between the layers in the optical film, so that the optical film has better performance.

[0044] Specifically, an embodiment of the present invention provides a method for preparing an optical film, comprising:

[0045] S100, blending polyimide, polycarbonate, and polymethyl methacrylate and then melt-extrude the mixture to obtain a base film layer;

[0046] S200, sequentially performing plasma treatment and sputtering treatment on the base film layer to obtain an optical thin film;

[0047] Among them, S200 includes:

[0048] S210, using oxygen as plasma gas to perform plasma treatment on the base film layer, and then cooling to room temperature to obtain a first intermediate film layer;

[0049] S220, performing a first sputtering treatment on the first intermediate film layer in an argon atmosphere using a silicon dioxide target to obtain a second intermediate film layer;

[0050] S230, using a titanium target material to perform a second sputtering treatment on the second intermediate film layer in a mixed gas atmosphere of argon and oxygen to obtain an optical thin film.

[0051] Preferably, the embodiment of the present invention adopts material blending, plasma treatment and sputtering treatment to significantly improve the overall performance of the optical film. First, polyimide, polycarbonate and polymethyl methacrylate are blended. Polyimide is a high-performance polymer with excellent thermal stability, chemical stability and mechanical strength. Polyimide accounts for a major proportion in the base film layer, giving the film high temperature resistance and mechanical toughness; polycarbonate not only provides excellent optical transparency and impact toughness, but also improves the flexibility of the base film layer, and can also alleviate the high rigidity of the polyimide material, providing a certain flexibility for the optical film to adapt to different application environments; polymethyl methacrylate provides high optical transparency and good processability, and plays a filling and softening role in the base film layer. Its high optical properties are crucial to enhancing the overall optical effect of the base film layer; the blending of the three polymers combines their respective Advantages: a base film layer with high mechanical strength, good optical transparency and good thermal stability is formed, which is suitable for multi-band optical applications. Melt extrusion can provide a uniform film structure for the optical film, avoiding the degradation of optical performance due to uneven mixing. The mass ratio of polyimide, polycarbonate and polymethyl methacrylate is preferably (6-7): (2-3): 1, so that the base film layer has a heat resistance of up to 300°C, which is suitable for sputtering coating and subsequent heat treatment processes. A high proportion of polyimide provides sufficient rigidity, and the appropriate addition of polycarbonate and polymethyl methacrylate improves flexibility. The base film layer exhibits good mechanical stability under bending and impact conditions. The addition of polycarbonate and polymethyl methacrylate ensures high light transmittance and meets the multi-band response requirements of the optical film. The refractive index can be adjusted to 1.5-1.6 after the materials are mixed, which is suitable for the design requirements of the multi-layer film.

[0052] Plasma treatment can form chemical bonds with the sputtered coating, further improving the interface stability, thereby improving the adhesion of the base film layer to the sputtered coating and preventing the film layer from peeling off. Oxygen can be used as the plasma gas to introduce oxygen groups such as -OH, -COOH, etc., to activate the surface of the base film layer, increase the surface free energy, and improve the affinity; Sputtering treatment is to use high-energy plasma to bombard the target material so that the target atoms or molecules are detached from the surface and deposited on the substrate to form a thin film. It can accurately control the thickness and composition of the film layer and is suitable for the preparation of optical films. It can deposit the film at a lower temperature to avoid thermal damage to the flexible substrate material. At the same time, the sputtered film layer can cover irregular surfaces more evenly and improve the optical properties of the film. It is preferred to use radio frequency magnetron sputtering for sputtering treatment; the first sputtering treatment is the deposition of a silicon dioxide layer, using a SiO2 target material for sputtering deposition in an argon atmosphere, using a pure argon environment to ensure that the SiO2 layer is uniformly deposited without the generation of additional oxides, and can form a highly transparent, low refractive index first coating, which can provide anti-reflection function for optical films, reduce light loss, and increase The invention can strengthen the anti-oxidation and moisture resistance of the optical film and improve the environmental adaptability; the second sputtering treatment is the deposition of the titanium dioxide layer, and the titanium target is used for sputtering deposition in a mixed gas of argon and oxygen. The crystallinity and refractive index of the TiO2 film are optimized by mixing argon and oxygen, and a high refractive index TiO2 film layer is generated. The high refractive index TiO2 layer is alternately formed with the low refractive index SiO2 layer to achieve the interference effect and improve the multi-band optical performance. The photocatalytic effect of TiO2 can provide a certain self-cleaning function for the optical film and increase the anti-fouling property of the film; the combination of SiO2 and TiO2 forms a typical high and low refractive index alternating structure, provides excellent anti-reflection performance, improves the imaging quality of the optical element, and has interference filtering characteristics, thereby achieving high transmittance, which is suitable for multi-band optical response from ultraviolet to near infrared; the base film layer of the optical film of the embodiment of the present invention optimizes the mechanical properties and optical properties by melt blending, and improves the coating adhesion by plasma treatment; two layers of sputtering coating are formed by two sputtering treatments, giving the film excellent optical transmittance and anti-reflection performance.

[0053] Preferably, in S210, during the preparation process of the optical film, the plasma treatment stage significantly improves the surface properties of the base film layer by optimizing the oxygen flow rate, power, pressure and time, thereby laying a good foundation for subsequent sputtering treatment and coating adhesion;

[0054] The oxygen flow rate determines the concentration of oxygen ions and free radicals in the plasma, thus affecting the degree of chemical activation on the surface of the base film layer. The appropriate oxygen flow rate can balance the surface etching and activation effects, and avoid damage to the base film layer while forming oxygen groups. In addition, the introduction of oxygen improves the hydrophilicity of the surface of the base film layer, increases the surface free energy, and facilitates the subsequent adhesion of SiO2 and TiO2. Therefore, the oxygen gas flow rate is 20sccm-50sccm, which can achieve better plasma treatment effects.

[0055] The power of plasma treatment affects its excitation energy and surface modification efficiency. If the power of plasma treatment is too low, the plasma density is insufficient and the surface cannot be effectively activated. If the power of plasma treatment is too high, it may cause excessive etching or damage to the surface of the base film layer. Therefore, the power of plasma treatment is 60W-100W, which can ensure that the plasma can effectively excite oxygen molecules to produce active seeds such as oxygen ions O- and oxygen free radicals, achieve efficient surface modification, and evenly generate active groups without damaging the mechanical properties of the base film layer to improve the adhesion performance.

[0056] The pressure of plasma treatment affects the plasma density and the collision frequency of ions. At lower pressures, the plasma density is lower, but the energy of active ions is higher; at higher pressures, the plasma density increases, but the average energy of ions decreases. Therefore, the pressure of plasma treatment is 0.1 Torr-0.5 Torr, which can balance the ion density and active ion energy, ensure sufficient surface modification depth, avoid damage to the base film surface due to excessive energy input, generate uniform plasma, ensure consistent surface modification of the entire base film layer, and improve the optical properties and uniformity of the overall film.

[0057] The plasma treatment time determines the depth and range of the surface activation degree. A time that is too short is not enough to significantly increase the surface free energy; a time that is too long may lead to excessive etching of the base film layer. The plasma treatment time is 1min-3min, and a large number of oxygen groups can be generated on the surface of the base film layer through plasma activation to form a uniform and highly active surface, ensuring that the subsequent sputtering layer forms a strong bond with the base film layer without having a significant negative impact on the mechanical properties of the base film layer; the surface after oxygen plasma treatment has better uniformity, the deposition rate of SiO2 and TiO2 layers is more stable during sputtering treatment, and the film defects are reduced.

[0058] Preferably, in S220, the first sputtering process uses a SiO2 target material for sputtering, and by optimizing key parameters such as argon gas flow, power and pressure, it can ensure that the film has a high-quality low-refractive index SiO2 layer, thereby improving the optical and mechanical properties of the film;

[0059] Argon is the main working gas in sputtering. Its flow rate affects the plasma density and deposition rate of sputtered particles during the sputtering process. The gas flow rate of argon is 20sccm-40sccm, which balances the sputtering rate and film quality, maintains a stable plasma, improves sputtering efficiency, avoids excessive plasma scattering caused by excessive gas flow, and thus forms an uneven film layer, ensuring excellent optical properties and mechanical strength.

[0060] The power of the first sputtering treatment determines the sputtering rate of the target material and the kinetic energy of the sputtering particles. The lower the power, the slower the deposition rate, and the denser and smoother the film layer. The higher the power, the stronger the kinetic energy of the sputtering particles and the faster the deposition rate, but it may cause an increase in the internal stress of the film. The power of the first sputtering treatment is 100W-300W, which can generate high-quality SiO2 film layers with a flat and crack-free film surface and stable optical properties, which helps prevent film granulation or base film damage caused by excessive power, and can simultaneously meet the requirements of light transmittance and mechanical stability.

[0061] During the first sputtering treatment, the working gas pressure affects the sputtering path and deposition behavior of the target particles. If the pressure is low, the kinetic energy of the target sputtering particles is high, and it is easy to generate a dense film layer, but the deposition rate is slow. If the pressure is high, the collision frequency between particles increases, and the deposition rate is accelerated, but voids and film defects may be introduced. The pressure of the first sputtering treatment is 2Torr-6Torr, the sputtering efficiency is improved, and the uniform deposition of the thin film can be completed faster. At this time, the deposition rate of SiO2 can reach 1nm / min-5nm / min, which can form a dense SiO2 film layer with better wear resistance and corrosion resistance, and can reduce the high-energy damage of the sputtering particles, while avoiding the generation of excessive pores during the deposition process.

[0062] Preferably, in S230, the second sputtering process uses a titanium target, and the second sputtering process is performed in an argon and oxygen mixed atmosphere to deposit a TiO2 film layer. By optimizing parameters such as argon flow rate, oxygen flow rate, power and pressure, a high-quality high-refractive index film layer can be obtained, thereby improving the overall performance of the optical film;

[0063] The gas flow rate of argon is 20sccm-40sccm, which can form a dense film structure while ensuring the sputtering rate, maintain the uniformity of plasma during the sputtering process, and ensure the uniform thickness and consistent optical properties of the film; the gas flow rate of oxygen is 5sccm-15sccm. Oxygen is a necessary component for the formation of TiO2 film. Reasonable oxygen concentration can obtain a uniform and highly transparent TiO2 film, improve the optical transmittance of the film, prevent excessive stress in the film, and avoid cracks or peeling. The power of the second sputtering treatment is 100W-300W, which can generate a smooth and uniform TiO2 film with a high refractive index and stable optical properties, avoiding excessive power causing film granulation or base film damage; the pressure of the second sputtering treatment is 2Torr-6Torr, which accelerates the deposition rate. At this time, the deposition rate of TiO2 can reach 1nm / min-5nm / min, forming a dense, smooth, high-refractive-index TiO2 film while maintaining a certain film uniformity.

[0064] Furthermore, between S220 and S230, there is also:

[0065] S221, performing annealing treatment on the second intermediate film layer.

[0066] Preferably, an annealing treatment is added between S220 and S230 to heat treat the second intermediate film layer, which can effectively improve the performance of the film layer. Due to the high-energy deposition of film particles during the sputtering process, large internal stresses will accumulate in the film, which may cause film warping, cracking or peeling problems, affecting the adhesion and overall stability of subsequent coatings. Annealing can eliminate the internal stress in the film through thermal diffusion and rearrangement of the atomic structure, making the film layer more stable and having a stronger interface with the base film layer or subsequent film layer; in the first sputtering process, the initial SiO2 film The structure may have more pores or low density. Annealing can improve the density of the film layer and enhance its mechanical strength, wear resistance and corrosion resistance by promoting the sintering of particles and crystal rearrangement. The SiO2 film layer formed by the first sputtering treatment may contain a certain amount of non-stoichiometric substances such as silicon dioxide. Annealing can promote the stoichiometric ratio of the film to be more accurate, improve the optical transparency and refractive index stability of the film layer, and optimize its anti-reflection performance. Annealing treatment can also reduce the roughness of the film surface, making the surface smoother, which is conducive to the uniform deposition of the subsequent TiO2 film layer.

[0067] Preferably, the annealing treatment is carried out in an oxygen atmosphere, which provides a sufficient oxidation environment for the stoichiometric ratio of the film, and the suboxide in the film is oxidized to ensure the formation of high-purity SiO2, thereby improving the optical properties, and the pure oxide film layer is more stable and has stronger anti-aging ability in high temperature, high humidity or chemical corrosion environment; and the oxidation process inhibits the expansion of surface defects or non-uniform areas, making the film smoother and flatter, which is conducive to the adhesion of subsequent films;

[0068] The annealing temperature is 300℃-500℃, more suboxides in the film layer are completely oxidized, and the internal stress is effectively eliminated and the film densification is promoted. Some pores in the film layer structure are filled, which can make it smoother and prevent the film substrate from being degraded due to high temperature. At the same time, it can also enhance the mechanical strength, wear resistance and high temperature resistance of the film, and improve the anti-reflection performance of the optical film;

[0069] The annealing time is 1h-3h, which is sufficient to complete the oxidation densification of the surface layer of the film, promote the oxidation reaction and molecular rearrangement in the deep layer of the film, ensure the accuracy of the stoichiometric ratio, provide sufficient energy to release the internal stress of the film, and improve the crack resistance and mechanical stability of the film.

[0070] Furthermore, in S200, after the sputtering treatment, the method further includes: using a modified nano titanium dioxide solution for coating treatment; the preparation method of the modified nano titanium dioxide solution includes:

[0071] S201, dissolving nano titanium dioxide in an ethanol aqueous solution, adjusting the pH, and performing a first stirring treatment to obtain a nano titanium dioxide solution;

[0072] S202, adding the hexadecyltrimethoxysilane solution dropwise to the nano-titanium dioxide solution, and performing centrifugal treatment and purification treatment in sequence to obtain a modified nano-titanium dioxide solution.

[0073] Preferably, hexadecyltrimethoxysilane is a surfactant, and its silane group reacts with the active hydroxyl group on the surface of nano-titanium dioxide to form a stable chemical bond. After modification, a hydrophobic organic molecular layer is formed on the surface of the nano-titanium dioxide particles, which improves its dispersibility and coating stability in the solution. The contact angle of the hydrophobic molecular layer surface is greater than 120°, which improves the anti-fouling performance of the TiO2 coating. The size of the modified nano-titanium dioxide particles is maintained in the range of 20-30nm, which is conducive to the formation of a uniform coating. The use of modified nano-titanium dioxide solution for coating not only significantly enhances the anti-fouling, UV protection and weather resistance of the optical film, but also further optimizes its optical properties and mechanical stability.

[0074] Preferably, the mass ratio of nano-titanium dioxide to ethanol aqueous solution is 1:(10-25), which can effectively disperse nano-titanium dioxide; the surface of nano-titanium dioxide particles usually contains a large number of hydroxyl groups, and its surface activity is optimal under acidic conditions. Therefore, adjusting the pH to 4-5 is conducive to the hydrolysis and condensation reaction of hexadecyltrimethoxysilane, improving the modification efficiency, and providing a uniform particle base for the subsequent silane coupling agent reaction;

[0075] The rotation speed of the first stirring treatment is 450rpm-500rpm, which can provide appropriate shear force during the dispersion of nano-titanium dioxide to prevent particle agglomeration and ensure stirring uniformity; the time of the first stirring treatment is 4h-5h, which ensures that the nano-titanium dioxide is evenly dispersed in the solution and avoids local agglomeration in a high-concentration system. The temperature of the first stirring treatment is preferably 70°C-80°C, which can increase the solvent volatilization rate and accelerate the chemical reaction process;

[0076] The concentration of the hexadecyltrimethoxysilane solution is 15wt.%, which can provide enough silane coupling agent to participate in the reaction and avoid secondary coverage of the particle surface caused by excessive reaction. The dripping rate of the hexadecyltrimethoxysilane solution is controlled to 1mL / min-2mL / min, which can prevent the local reaction from being too fast, resulting in particle agglomeration or uneven modification.

[0077] The purification treatment is repeated 2-3 times to effectively remove unreacted HDTMS and other impurities to ensure the purity of the modified layer. The purification treatment is preferably performed at a centrifugal speed of 4000rpm-6000rpm. After the purification treatment, anhydrous ethanol is used to clean the surface of the particles to further remove unbound organic molecules and improve the stability of the solution.

[0078] Embodiment 1

[0079] This embodiment provides an optical film, and the preparation method thereof comprises the following steps:

[0080] S100, blending polyimide, polycarbonate, and polymethyl methacrylate in a mass ratio of 6:2:1 and then melt-extruding to obtain a base film layer;

[0081] S200, sequentially performing plasma treatment and sputtering treatment on the base film layer to obtain an optical thin film;

[0082] Among them, S200 includes:

[0083] S210, using oxygen with a gas flow rate of 20 sccm as plasma gas, performing plasma treatment on the base film layer for 1 minute, the pressure of the plasma treatment is 0.1 Torr, the power is 60 W, and the base film layer is cooled to room temperature to obtain a first intermediate film layer;

[0084] S220, using a silicon dioxide target material in an argon atmosphere with a gas flow rate of 20 sccm, performing a first sputtering treatment on the first intermediate film layer, the power of the first sputtering treatment being 100 W and the pressure being 2 Torr, to obtain a second intermediate film layer;

[0085] S230. Use a titanium target material in a mixed gas atmosphere of argon and oxygen, wherein the gas flow rate of argon is 20 sccm and the gas flow rate of oxygen is 5 sccm, to perform a second sputtering treatment on the second intermediate film layer. The power of the second sputtering treatment is 100 W and the pressure is 2 Torr to obtain an optical thin film.

[0086] Embodiment 2

[0087] This embodiment provides an optical film, and the preparation method thereof comprises the following steps:

[0088] S100, blending polyimide, polycarbonate, and polymethyl methacrylate in a mass ratio of 7:3:1 and then melt-extruded to obtain a base film layer;

[0089] S200, sequentially performing plasma treatment and sputtering treatment on the base film layer, and then coating the base film layer with a modified nano-titanium dioxide solution to obtain an optical film;

[0090] Among them, S200 includes:

[0091] S210, using oxygen with a gas flow rate of 50 sccm as plasma gas, performing plasma treatment on the base film layer for 3 minutes, the pressure of the plasma treatment is 0.5 Torr, the power is 100 W, and cooling to room temperature to obtain a first intermediate film layer;

[0092] S220, using a silicon dioxide target material in an argon atmosphere with a gas flow rate of 40 sccm, performing a first sputtering treatment on the first intermediate film layer, the power of the first sputtering treatment being 300 W and the pressure being 6 Torr, to obtain a second intermediate film layer;

[0093] S230, using a titanium target in a mixed gas atmosphere of argon and oxygen, wherein the gas flow rate of argon is 40 sccm and the gas flow rate of oxygen is 15 sccm, performing a second sputtering treatment on the second intermediate film layer, the power of the second sputtering treatment is 300 W, and the pressure is 6 Torr, and then using a modified nano titanium dioxide solution for coating treatment to obtain an optical thin film;

[0094] Between S220 and S230, there are also:

[0095] S221, annealing the second intermediate film layer in an oxygen atmosphere for 1 hour at a temperature of 300° C.;

[0096] The preparation method of modified nano titanium dioxide solution comprises:

[0097] S201, dissolving nano-titanium dioxide in an ethanol aqueous solution, wherein the mass ratio of nano-titanium dioxide to the ethanol aqueous solution is 1:10, adjusting the pH to 4, and performing a first stirring treatment at a speed of 450 rpm for 4 hours at a temperature of 70° C. to obtain a nano-titanium dioxide solution;

[0098] S202. Add a 15wt.% hexadecyltrimethoxysilane solution dropwise into the nano-titanium dioxide solution at a dropping rate of 1mL / min, and perform centrifugal treatment and purification treatment in sequence. The purification treatment is performed at a centrifugal speed of 4000rpm and repeated twice. After the purification treatment, use anhydrous ethanol to clean the particle surface to obtain a modified nano-titanium dioxide solution.

[0099] Embodiment 3

[0100] This embodiment provides an optical film, and the preparation method thereof comprises the following steps:

[0101] S100, blending polyimide, polycarbonate, and polymethyl methacrylate in a mass ratio of 7:3:1 and then melt-extruded to obtain a base film layer;

[0102] S200, sequentially performing plasma treatment and sputtering treatment on the base film layer, and then coating the base film layer with a modified nano-titanium dioxide solution to obtain an optical film;

[0103] Among them, S200 includes:

[0104] S210, using oxygen with a gas flow rate of 40 sccm as plasma gas, performing plasma treatment on the base film layer for 3 minutes, the pressure of the plasma treatment is 0.4 Torr, the power is 80 W, and the base film layer is cooled to room temperature to obtain a first intermediate film layer;

[0105] S220, using a silicon dioxide target material in an argon atmosphere with a gas flow rate of 30 sccm, performing a first sputtering treatment on the first intermediate film layer, the power of the first sputtering treatment being 200 W and the pressure being 5 Torr, to obtain a second intermediate film layer;

[0106] S230, using a titanium target in a mixed gas atmosphere of argon and oxygen, wherein the gas flow rate of argon is 30 sccm and the gas flow rate of oxygen is 12 sccm, performing a second sputtering treatment on the second intermediate film layer, the power of the second sputtering treatment is 200 W, and the pressure is 5 Torr, and then using a modified nano titanium dioxide solution for coating treatment to obtain an optical thin film;

[0107] Between S220 and S230, there are also:

[0108] S221, annealing the second intermediate film layer in an oxygen atmosphere for 3 hours at a temperature of 500° C.;

[0109] The preparation method of modified nano titanium dioxide solution comprises:

[0110] S201, dissolving nano-titanium dioxide in an ethanol aqueous solution, wherein the mass ratio of nano-titanium dioxide to the ethanol aqueous solution is 1:25, adjusting the pH to 5, and performing a first stirring treatment at a speed of 500 rpm for 5 hours at a temperature of 80° C. to obtain a nano-titanium dioxide solution;

[0111] S202. Add a 15wt.% hexadecyltrimethoxysilane solution dropwise to the nano-titanium dioxide solution at a dropping rate of 2mL / min, and perform centrifugal treatment and purification treatment in sequence. The purification treatment is performed at a centrifugal speed of 6000rpm and repeated 3 times. After the purification treatment, use anhydrous ethanol to clean the particle surface to obtain a modified nano-titanium dioxide solution.

[0112] Performance Testing

[0113] The optical films in Examples 1-3 were sampled and subjected to the following tests. The test results are shown in Table 1:

[0114] Optical performance test: Use UV-visible spectrophotometer to measure the transmittance in visible light and infrared light regions;

[0115] Contact angle test: Use a contact angle meter to measure the static contact angle of a water drop on the film surface;

[0116] Adhesion test: Use the tape peeling method to test the integrity of the optical film;

[0117] Thermal stability test: The thermal decomposition temperature of the film was measured using a thermogravimetric analyzer.

[0118] Table 1

[0119]

[0120] It can be seen from Table 1 that the optical films in Examples 1-3 all have good properties, especially the optical films in Examples 2-3. This may be because the optical films in Examples 2-3 have been annealed, so that the SiO2 layer and the TiO2 layer have good adhesion, thereby making the performance of the optical films better; the optical films in Examples 2-3 are also coated with a modified nano-titanium dioxide coating to further increase the contact angle, thereby having better anti-fouling performance.

[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing an optical film, characterized in that: include: S100, blending polyimide, polycarbonate, and polymethyl methacrylate and then melt-extrude the mixture to obtain a base film layer; S200, sequentially performing plasma treatment and sputtering treatment on the base film layer to obtain the optical film; Wherein, the S200 includes: S210, using oxygen as plasma gas, performing the plasma treatment on the base film layer, and then cooling the base film layer to room temperature to obtain a first intermediate film layer; S220, performing a first sputtering treatment on the first intermediate film layer in an argon atmosphere by using a silicon dioxide target to obtain a second intermediate film layer; S230, using a titanium target material to perform a second sputtering treatment on the second intermediate film layer in a mixed gas atmosphere of argon and oxygen to obtain the optical thin film.

2. The preparation method according to claim 1, characterized in that: In the S210, The oxygen gas flow rate is 20 sccm-50 sccm; and / or The power of the plasma treatment is 60W-100W; and / or The pressure of the plasma treatment is 0.1 Torr-0.5 Torr; and / or The plasma treatment time is 1 min-3 min.

3. The preparation method according to claim 1, characterized in that: In the S220, The gas flow rate of the argon gas is 20 sccm-40 sccm; and / or The power of the first sputtering process is 100W-300W; and / or The pressure of the first sputtering process is 2 Torr-6 Torr.

4. The preparation method according to claim 1, characterized in that: In the S230, The gas flow rate of the argon gas is 20 sccm-40 sccm; and / or The gas flow rate of oxygen is 5 sccm-15 sccm; and / or The power of the second sputtering process is 100W-300W; and / or The pressure of the second sputtering process is 2 Torr-6 Torr.

5. The preparation method according to claim 1, characterized in that: The steps between S220 and S230 also include: S221, performing annealing treatment on the second intermediate film layer.

6. The preparation method according to claim 5, characterized in that: The annealing treatment is performed in an oxygen atmosphere; and / or The annealing temperature is 300°C-500°C; and / or The annealing time is 1h-3h.

7. The preparation method according to claim 1, characterized in that: In the S200, after the sputtering process, the following steps are further included: Using modified nano titanium dioxide solution for coating treatment; The preparation method of the modified nano titanium dioxide solution comprises: S201, dissolving nano titanium dioxide in an ethanol aqueous solution, adjusting the pH, and performing a first stirring treatment to obtain a nano titanium dioxide solution; S202, adding the hexadecyltrimethoxysilane solution dropwise to the nano-titanium dioxide solution, and performing centrifugal treatment and purification treatment in sequence to obtain the modified nano-titanium dioxide solution.

8. The preparation method according to claim 7, characterized in that: The mass ratio of the nano titanium dioxide to the ethanol aqueous solution is 1:(10-25); and / or The pH is adjusted to 4-5; and / or The rotation speed of the first stirring process is 450rpm-500rpm; and / or The first stirring treatment time is 4h-5h; and / or The concentration of the hexadecyltrimethoxysilane solution is 15 wt.%; and / or The purification process was repeated 2 to 3 times.

9. The preparation method according to claim 1, characterized in that: In the S100, The mass ratio of the polyimide, the polycarbonate, and the polymethyl methacrylate is (6-7):(2-3):

1.

10. An optical film, characterized in that: The optical film is prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Cited By

  • Low-sheet-resistance high-light-transmittance ITO coating film and preparation method thereof

    CN120158711A